A microeconomic analysis of the declining labor share in Japan - Kyoji Fukao; Koji Ito; Cristiano Perugini (Asian Development Bank Institute (ADBI), 2019)
The labor share in Japan has been declining significantly over the last three decades, accompanied by persistent stagnation and an unprecedented increase in economic inequalities. Since these dynamics are likely to be interrelated, understanding the drivers of the labor share might contribute significantly to the Japanese economic and policy debate. Surprisingly, the existing literature on the labor share in Japan is rather limited and confined to country or industry studies. We first attempt to analyze the drivers of the labor share in Japan at the firm level. To this aim, we employ a panel of manufacturing firms from the Basic Survey of Japanese Business Structure and Activities, spanning from 2001 to 2012. By means of panel data estimators, we show how, besides technological variables, firms' labor share depends significantly on the share of regular workers, on the importance of firms' international engagement, and on various institutional settings of the product and labor markets.
Keywords: D33; F61; J30; L11; 330; labor share; firm-level analysis; Japan; panel data